Territorial organization of agricultural production: theory and methodology (Journal of Economic Research & Business Administration, 2016)
The article discusses the theoretical and methodological aspects ofthe territorial organization of agriculture. The authors examine a numberof theories, which cover certain aspects of the territorial distribution ofagricultural industries, and studying its individual or specific issues (eg,the impact of agricultural land relative locations of the city (market) onthe yield and specialization of agriculture). Revealing the essence of thesetheories, the authors note that the inclusion of the underlying principles ofthese theories make it possible to effectively use agricultural productionfactors. The main task of the territorial organization of a mutual adaptationof agricultural production areas and production, creation of favorableconditions for effective space management through efficient deploymentof the organization of production and use of production factors.Highlighted the concept of adaptive intensification of agriculture, whichis characterized by a complex effect of natural, social, economic and technologicalfactors on the territorial system of agriculture. This theory implies adifferentiated approach to the spatial distribution of agricultural production,depending on the combination of natural and socio-economic conditions.
Keywords: agriculture; territorial organization; division of labor; regional economy; territory.